Backbone Configuration and Electronic Property Tuning of Imide‐Functionalized Ladder‐Type Heteroarenes‐Based Polymer Acceptors for Efficient All‐Polymer Solar Cells. (19th February 2022) - Liu, Bin; Wang, Yingfeng; Sun, Huiliang; Gámez‐Valenzuela, Sergio; Yan, Zhenglong; Feng, Kui; Uddin, Mohammad Afsar; Koh, Changwoo; Zhou, Xin; López Navarrete, Juan Teodomiro; Ruiz Delgado, María Carmen; Meng, Hong; et al.
Abstract: Electron‐deficient ladder‐type π‐conjugated systems are highly desired for constructing polymer acceptors due to their unique electronic properties. Herein, two series of polymer acceptors PBTIn‐(F)T ( n  = 1–4) based on imide‐functionalized ladder‐type heteroarenes (BTIn) with tunable conjugation length are synthesized. Effects of their backbone configuration and electronic properties on film morphology and performance of all‐polymer solar cells (all‐PSCs) are systematically investigated through theoretical computation, Raman spectroscopy, grazing incidence wide‐angle X‐ray scattering, etc. It is found that the ladder‐type heteroarene size extension and polymer backbone fluorination gradually lower the frontier molecular orbital energy levels, leading to progressive bandgap narrowing with more efficient exciton dissociation. Furthermore, the centrosymmetric and axisymmetric characteristics of BTIn result in distinct backbone configuration with varied self‐aggregation and crystalline phases, hence determining the blend film morphology. The highest efficiencies in these two series are attained from PBTI3‐T and PBTI3‐FT with a curved backbone configuration. PBTI4‐(F)T with further extended heteroarenes shows linear backbone, negatively affecting film morphology and efficiency. This study provides fundamental material structure‐device performance correlations for ladder‐type heteroarenes‐based polymer acceptors for the first time and demonstrates that more extended ladder‐type backbones do not necessarily improve the device performance, offering guidelines for designing polymer acceptors to maximize all‐PSC performance. Abstract : The effects of electronic property and backbone configuration of the imide‐functionalized ladder‐type heteroarenes‐based polymer acceptors on performance of all‐polymer solar cells are investigated. Heteroarene size extension and polymer backbone fluorination not only lower the frontier molecular orbital energy levels but also affect symmetric characteristics of PBTIn‐(F)T. The highest efficiencies are attained from PBTI3‐(F)T polymers with a curved backbone configuration.